2015
DOI: 10.1111/adb.12324
|View full text |Cite
|
Sign up to set email alerts
|

α2A‐Adrenergic receptor polymorphisms and mRNA expression levels are associated with delay discounting in cocaine users

Abstract: Cocaine users characteristically display preferences for smaller immediate rewards over larger delayed rewards, and this delay discounting (DD) has been proposed as an endophenotype of cocaine addiction. Recent evidence suggests that the norepinephrine system and more specifically the α -adrenergic receptor (ADRA2A) are impacted by chronic cocaine use while also being potentially involved in the neural mechanisms underlying DD. Hence, we investigated the effects of ADRA2A polymorphisms and ADRA2A mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Interestingly, specific impairments in attentional set-shifting were reported for noradrenergic but not cholinergic deafferentation of the medial prefrontal cortex—the homolog of the primate dorsolateral prefrontal cortex in rats 54 . Given that we previously proposed that CU might show neuroplastic adaptations in the noradrenaline system 55 , 56 one could speculate that not only cocaine but specifically a cocaine–aminorex combination can disrupt the noradrenaline transmission. Moreover, medically prescribed levamisole intake is supposed to cause multifocal inflammatory leukoencephalopathy 57 , 58 , a disease associated with white matter lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, specific impairments in attentional set-shifting were reported for noradrenergic but not cholinergic deafferentation of the medial prefrontal cortex—the homolog of the primate dorsolateral prefrontal cortex in rats 54 . Given that we previously proposed that CU might show neuroplastic adaptations in the noradrenaline system 55 , 56 one could speculate that not only cocaine but specifically a cocaine–aminorex combination can disrupt the noradrenaline transmission. Moreover, medically prescribed levamisole intake is supposed to cause multifocal inflammatory leukoencephalopathy 57 , 58 , a disease associated with white matter lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These links to dopamine-related loci are consistent with preclinical studies that implicate dopamine neurotransmission with delay discounting. Of note, however, serotonin and norepinephrine also appear to play important roles (50; 51; 74) and two studies have found associations between polymorphisms in serotonin and noradrenergic genes and delay discounting preferences (75; 76). Although genetic studies are at an early stage, the current findings support the need for further attempts to examine whether delay discounting can be used to understand one pathway for genetic influences on ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular imaging studies investigating alterations in the serotonin and noradrenaline system in cocaine users are lacking, with one exception: a single positron emission tomography study has shown that norepinephrine transporter density in the thalamus is upregulated in cocaine users (Ding et al, 2010). In line with a recent publication demonstrating that increased delay discounting in cocaine users might be explained by an interaction between a genetic variation of an alpha-adrenergic receptor and cocaine use (Havranek et al, 2016), this finding suggests that adaptations in the norepinephrine system might also account for some cognitive changes found in cocaine users. Another recent study indicates that genetic variation in serotonin transporters also plays an important role in the development of working memory deficits in chronic cocaine users (Havranek et al, 2015); thus, changes in the serotonin system might be involved in cocaine-related cognitive impairments.…”
Section: Neurobiological Linkage Between Cocaine Use and Cognitive Fumentioning
confidence: 91%